Late presentation of chronic hepatitis B virus in Spain: a country with access to therapy. (13th November 2019) - Picchio, C; Roel, E; Buti, M; Lens, S; Andrade, R J; Crespo, J; Calleja, J L; Simon, M A; Lazarus, J V
Abstract: Background and aims: Chronic infection with hepatitis B virus (HBV) can progress to liver cirrhosis and lead to complications such as decompensated liver disease, hepatocellular carcinoma and liver-related death. Antiviral agents against HBV are very effective in suppressing viremia and greatly reduce the risk of complications if treatment is initiated before the onset of advanced liver disease. The aim of this study is to assess the prevalence of late presentation in leading hospitals across Spain. Methods: Retrospective cohort study of patients seeking first time care with a liver specialist at six tertiary Spanish hospitals, with 2018 data. Late presentation (LP) included advanced liver disease (ALD) defined by significant fibrosis (≥ F3 assessed by either APRI score > 1.5, FIB-4 > 3.2, transient elastography (FibroScan) > 9.5 kPa or biopsy ≥ METAVIR stage F3) with no previous antiviral treatment and late-stage liver disease (LSLD) was defined by the presence of decompensated cirrhosis and/or hepatocellular carcinoma. Prevalence of ALD and LSLD at first consultation, demographics, and associated risk factors were analysed. Results: 203 patients chronically infected with HBV were included. Advanced liver disease was detected in 14.8% and late stage liver disease was observed in 6.1% of cases. 57.1% of the cases were male. The majority of those with HBV were non-Spanish (53.7%). The median age was 47 and the median of years from diagnosis to specialist care was 1 (IQR 7). 58.6% of patients were referred from primary care and 3.7% cases had hepatocellular carcinoma upon presentation for care. Conclusions: Late presentation with HBV is common in Spain, particularly for the foreign-born population, despite full access to antiviral therapy for HBV in the country. In order to rectify this health systems failure, improve outcomes and reach the viral hepatitis elimination goal adopted by WHO in 2016, strategies to reduce late presentation to care are essential. Key messages: Early diagnosis of HBV is needed in order to rectify the health systems failure of late presentation to care. Interventions targeting foreign-born populations should be implemented to reduce late presentation to HBV care and treatment.